Assessment of level of Awareness regarding Thalassemia Major among Parents of Affected Children - Faizan Fazal, Mateen Arshad, Haris Mustafa, Muhammad Ebad Ur Rehman, Usama Tanveer, Faizan Fazal, Mateen Arshad, Haris Mustafa, Muhammad Ebad Ur Rehman, Usama Tanveer (Journal of Rawalpindi Medical College, 2021)
Background: Thalassemia major is amongst the most common genetic disorders in developing countries like Pakistan. This research project aims to assess the level of knowledge among people related to thalassemia and the number of thalassemia cases linked to consanguineous marriages. Materials and Methods: A cross-sectional study was conducted among parents (n=272) of thalassemia patients registered with Rawalpindi thalassemia welfare society, from June 2019 to September 2019. Parents of thalassemia major patients aged 1 to 16 years were included. Parents who were health care professionals or community workers, and with children who had some other genetic disorders along with thalassemia major were excluded. Non-probability consecutive sampling was used. Data were collected using a self-designed questionnaire that assessed the prevalence of thalassemia in relation to consanguineous marriages and awareness of thalassemia in parents of affected ones. Data were analyzed using Statistical Package for Social Sciences (SPSS), version 22, by applying descriptive statistics. Results: About 72% of the parents (n=214) had consanguineous marriages. None of them had a thalassemia screening test before their marriage. 98.5% of the parents said no awareness campaign had ever been conducted for thalassemia in their area. 50% of families believed that thalassemia had affected their children's interaction with other children of their age. Conclusion: This study reveals that parents of thalassemia-affected children are not aware of the high link between thalassemia and cousin marriages and the prevalence of premarital testing is almost none.